1995
DOI: 10.1042/bj3070749
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin-sensitive Ca2+-ATPases account for Ca2+ uptake to inositol 1,4,5-trisphosphate-sensitive and caffeine-sensitive Ca2+ stores in adrenal chromaffin cells

Abstract: In chromaffin cells of adrenal medulla, heterogeneity of Ca2+ stores has been suggested with respect to the mechanisms of Ca2+ uptake and release. We have examined Ca(2+)-ATPases responsible for loading of Ca2+ stores in these cells for their sensitivity to thapsigargin, a highly selective inhibitor of the SERCA [sarco(endo)plasmic reticulum calcium ATPase] family of intracellular Ca2+ pumps. Using immunostaining, we studied the distribution of Ca(2+)-ATPases, and of receptors for inositol 1,4,5-trisphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 60 publications
5
36
0
Order By: Relevance
“…Since the absence of a phosphorylated protein at 116 kDa allowed a more accurate measurement of the radioactivity selectively associated with the 100 kDa E~P, we routinely omitted Mg 2÷ in the further analysis of the 100 kDa phosphorylated intermediate. The distribution of the 100 kDa E~P in the submicrosomal fractions was analyzed using the isopycnic, discontinuous sucrose gradient characterized recently [12]. The distribution was broad, indicating the presence of Ca2+-ATPase in ER subcompartments spanning different buoyant densities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the absence of a phosphorylated protein at 116 kDa allowed a more accurate measurement of the radioactivity selectively associated with the 100 kDa E~P, we routinely omitted Mg 2÷ in the further analysis of the 100 kDa phosphorylated intermediate. The distribution of the 100 kDa E~P in the submicrosomal fractions was analyzed using the isopycnic, discontinuous sucrose gradient characterized recently [12]. The distribution was broad, indicating the presence of Ca2+-ATPase in ER subcompartments spanning different buoyant densities ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We studied the formation of Ca2*-ATPase phosphorylated intermediates (E ~ P) [15,16] in a preparation ofmicrosomes from bovine adrenal medulla described earlier [12,13]. The microsomes were incubated with [~'-32p]ATP, followed by PAGE in an acid gel system and autoradiography.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, BODIPY-FL-thapsigargin -binding sites coincided with those labeled with the anti-calnexin Ab. We [23] and others [34] reported that thapsigargin depleted Ca 2+ ions from store sites, from which Ca 2+ mobilization occurred in response to InsP 3 -generating receptor agonists. Thus the coincidence of BODIPY-FL-thapsigargin-binding sites with calnexin-like immunoreactive sites is consistent with the notion that the ER alone is responsible for InsP 3 -sensitive store sites in chromaffin cells.…”
Section: Discussionmentioning
confidence: 99%